INNOVATIVE ACTIVITY IN THE ROAD SECTOR AND THE STRATEGY FOR THE DEVELOPMENT OF SUCH ACTIVITY - A. V. Borovik; A. S. Sedova (Вестник СибАДИ)
Introduction. The process of innovative development of the road industry for the period 2012-2017 is analyzed in the article. It is proclaimed that for the development and arrangement of Russian roads during 6 years would be invested more than 11 trillion rubles in comparison with 6.4 trillion in 2012-2017. Thus, the significant increase in funding would lead to the fundamental change in the approaches to the planning of the innovation process.Materials and methods. The main shortcomings in the development of the innovative strategies in industry were demonstrated. The problem that the strategies have no interrelations between the goal, resources and time is formulated. All production systems operate in different conditions and are characterized by different levels of the resources consumption and, consequently, by different efficiency. At the same time, it is very difficult to formulate a goal in the absence of sufficiently accurate predicted performance parameters of production systems.Results. As a result, it is difficult to determine the effectiveness of the funds allocated for innovative development.Discussion and conclusion. Digitalization in the form of the production function is an effective management tool to improve the validity and effectiveness of the innovative development strategy in the road sector, to carry out current calculations monitoring and evaluation of the desired parameters accuracy.